Pressure drop and mass transfer in the structured cartridges with fiber-glass catalyst; Chemical Engineering Journal; Vol. 282: The XXI International Conference on Chemical Reactors CHEMREACTOR-21, 15 December 2015, Amsterdam - Lopatin S. A.; Mikenin P. E.; Pisarev D. A.; Baranov D. V.; Zazhigalov S. V.; Zagoruiko A. N. Andrey Nikolaevich (2015, 2015)
Title screen